The Readiness of the Early Childhood Education Institution Establishment in Terms of the Availability of Facilities and Infrastructure (A Case Study of playgroup Aisyiyah, Kabupaten Kudus) - Khikmah, Ainul; Mukminin, Amirul (BELIA: Early Childhood Education Papers, 2017)
The readiness was meant by physics and psychologist conditions to achieve the planning. In establishing Early Childhood Education, the important components were facilities and infrastructure. Good institution had good function of the facilities and infrastructure. It supported the teaching and learning process. The purposes of the study were to describe the readiness of playgroup establishment by looking at the availability of facilities and infrastructure and to describe the facilities and infrastructure management of playgroup Aisyiyah, Kabupaten Kudus.The study used qualitative method. The research took place in playgroup Aisyiyah V Papringan, playgroup Aisyiyah Terpadu Birrul Walidain and playgroup Aisyiyah Payaman. The research informants were the head master, teacher, and Aisyiyah committee. The data collecting was gathered by using interview, observation, field note, and documentation. The data analysis used data collection, data reduction, data display and data verifying. The validity was measured by using triangulation.The result showed that the first facility of the availability in playgroup establishment was the learning equipment. Infrastructure had not built yet, it could be a loan, lodging, and using other party building. The planning was done periodically. The availability was fulfilled by purchasing, loan, rental, granting, recycling, self-production, and recondition. The registration was written once in a month. The storage was in the storeroom, cupboard, and locker. In addition, it was treated periodically. The utilizing paid attention to the efficiency and effectiveness principles. The discontinuance of the institution was done by selling disposal of the facilities and infrastructure used.Hence, it could be concluded that the readiness of playgroup from the facilities and infrastructure sides were based on the learning equipments. The availability of the infrastructure was not built. The facilities and infrastructure management were through planning, provisioning, regulating, using, and erasing. For the institution, it would be good to pay attention the facilities and infrastructure elements when they would establish a playgroup.